Protective effects of butein on corticosterone-induced cytotoxicity in Neuro2A cells - Masanori Ohmoto; Yukina Shibuya; Shihori Taniguchi; Tomoki Nakade; Masaaki Nomura; Yuri Ikeda-Matsuo; Tohru Daikoku (IBRO Reports, 2020)
A functional understanding of the relationship between glucocorticoids and neuronal apoptosis induced by the production of reactive oxygen species (ROS) may lead to a novel strategy for the treatment or prevention of depression. Previous reports suggest that butein, a type of flavonoids, may be a potent candidate against depression-related neuronal cell apoptosis caused by oxidative stress; however, the protective effects of butein on damaged corticosterone (CORT)-treated neuronal cells has not been elucidated. In the present study, we examined the protective effect of butein on CORT-induced cytotoxicity and neurite growth during cell differentiation of mouse neuroblastoma Neuro2A (N2A) cells. Moreover, the effect on cultured cells by high concentrations of butein was confirmed. Our results demonstrate that CORT treatment significantly decreases cell viability and induces cell death. CORT was suggested to induce apoptosis via mitochondrial dysfunction and caspase-3 activation; this apoptosis may be attributed to DNA damage by ROS generation, found in this study to be significantly inhibited by pretreatment with butein. We found that CORT produced significant growth suppression of retinoic acid-induced neurite outgrowth in N2A cells; however, butein significantly increased neurite length and induced dose-dependent apoptotic cytotoxicity in N2A cells. This study suggests that low concentration of butein can prevent CORT-induced cytotoxicity in N2A cells, and provides preliminary results supporting some of the beneficial roles of butein in neuroprotection.